Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1002/jcp.1041610318
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone suppresses the differentiation of osteoprogenitor cells to osteoblasts, but enhances functional activities of mature osteoblasts in cultured rat calvaria cells

Abstract: The effects of thyroid hormone on osteoblastic differentiation and activity were studied in fetal rat calvaria (RC) cells cultured for up to 30 days in medium supplemented with thyroid hormone-depleted serum. In this condition, the cells proliferated and differentiated to form mineralized bone nodules (BN) and expressed osteoblastic markers such as alkaline phosphatase (ALP), osteocalcin (OCN), and osteopontin (OPN). The continuous presence of triiodothyronine (T3) at 10(-9)-10(-8) M in the medium inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 45 publications
3
35
1
1
Order By: Relevance
“…This finding was described in adults rats with hyperthyroidism (14). According to some researchers, thyroid hormones stimulate osteoblast synthesis and, thus, the voluminous aspect observed in the osteoblasts of offspring of rats treated with thyroxin may be a reflex of this action (30,31). Besides, a recent study demonstrated that stem cells of the bone marrow of hyperthyroid female rats show greater potential for differentiation in osteoblasts (31), justifying the presence of areas of hyperplasia and the consequent increase in the percentage of trabecular bone tissue observed in animals in this study.…”
Section: Discussionmentioning
confidence: 70%
“…This finding was described in adults rats with hyperthyroidism (14). According to some researchers, thyroid hormones stimulate osteoblast synthesis and, thus, the voluminous aspect observed in the osteoblasts of offspring of rats treated with thyroxin may be a reflex of this action (30,31). Besides, a recent study demonstrated that stem cells of the bone marrow of hyperthyroid female rats show greater potential for differentiation in osteoblasts (31), justifying the presence of areas of hyperplasia and the consequent increase in the percentage of trabecular bone tissue observed in animals in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Lack of this hormone or of its receptor results in severe developmental disturbances [36] but hyperthyroidism is known to increase bone cell functions and cause osteoporosis. At the cellular level, this hormone regulates many genes and their functions during the osteoblastic differentiation process like alkaline phosphatase and its activity [8,37] and OCN [7,9], and it additionally enhances the functional activity of differentiated osteoblasts [38]. The accelerated remodeling process encountered in hyperthyroidism could easily be explained by the fact that increased MMP-13 is synthesized thus enhancing the initiation of resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Control of proliferation could depend on the state of differentiation, the culture time (Stein & Lian 1993, Ohishi et al 1994 or the development of cell/cell contacts. In this study, we seeded cells at different densities, cultured them for 3 days and studied DNA synthesis by measuring [ 3 H]thymidine incorporation.…”
Section: Discussionmentioning
confidence: 99%